E-pedagogical design of a UK work-based learning programme - Raistrick, Claire (Proceedings of the International Conference on Networked Learning, 2012)
There is an increasing accent on using technology to facilitate learning as new technologies become more widely available, popularised and promoted. Similarly there is continuing emphasis on work-based learning as a means to develop highly skilled workers. This paper questions whether there is a convincing case for using networked learning in relation to a UK work-based learning programme and considers the availability of meaningful guidance. After considering the turn to online learning and establishing the case for pedagogically sound approaches this paper outlines philosophical approaches associated with the design of online learning. It then considers how this might be applied to Programme X, a post-graduate work-based learning diploma for regulatory professionals which is implemented via a tri-partite arrangement between learners, their employer and the university. Earlier consideration of Programme X ‘established that interaction can benefit learning’ and that there is a need ‘to root the programme more securely in learners’ practice’ (Raistrick, 2010, p. 341). In reviewing the potential for online learning it is important to consider what is required. Is it a community of practice? Or perhaps a collaborative approach? Alternatively does a definition of networked learning with its emphasis on connections and relationships allow the greatest potential to learn effectively? Similarly connectivism seems increasingly relevant. When tailoring the multitude of possibilities to the specifics of a particular situation where should educators start? Potential elements of an online learning design are illustrated to give a flavour of how this might look in a specific context. These consider: firstly, how Laurillard’s Conversational Framework might bridge learning needs between the existing approach to learning and a technologically-mediated one; secondly, how a series of weak ties established through entering into a learning dialogue using an online forum might hold potential for learning; and lastly how the interaction, connections and relationships afforded by creation of a patchwork text assessment might assist learners in blending formal and informal knowledge. The thinking illustrated here may be of interest to those considering use of networked learning to support work-based learning. What seems to matter most is to seek an approach that adds benefit, though this is part of the difficulty as the research findings are partial and context-specific. Gaps in the research evidence highlight the importance of researching practice to identify how to enhance the learning experience for both learners and educators.